Integrated Safety Implications for Project Management - Vanek, Michal; Tomaskova, Yveta; Senovsky, Michal; Krcmarska, Lucie (Communications - Scientific letters of the University of Zilina, 2013)
Safety insurance provisions in the broadest sense of the term belong among major tasks and challenges for a company management as well as any municipality administration. In the framework of the decision making process, the manager or administrator takes into account a lot of factors, among which – apart from safety risks – financial possibilities of the company or municipality are of major importance. The decisions made have a project character, and managers and administrators can take advantage of project management tools to be able to assess viability of the decisions suggested, as well as their implementation. This paper concentrates on the prior-to-investment process of the project management, and the paper’s focal point is in suggesting a method for technical and economic (cost efficiency) assessment of safety projects.